2017
DOI: 10.1097/jom.0000000000001130
|View full text |Cite
|
Sign up to set email alerts
|

“It's not an Obvious Issue, Is It?” Office-Based Employees’ Perceptions of Prolonged Sitting at Work

Abstract: This study has highlighted that in addition to personal determinants, the workplace environment and organizational culture have a key role in supporting employees' potential adoption of healthier sitting behavior in the workplace.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…If we had, I guess, other tasks that involved getting up for a period of time that would probably help as well.” Employee, non-intervention study [ 12 ] Social or organisational Barriers Barriers - Not wanting to stand out - Concern about disturbing co-workers - Concern that standing or moving perceived as not working by colleagues and managers - Leaders not convinced about benefits of reducing sedentary behaviour - Workplace culture not supportive of initiatives to reduce sitting - Financial investment associated with sit-stand workstations - Culture encourages siloing and use of email. - Cultural issues: “Asian culture” perceives standing to be aggressive - OHS concerns relating to sit-stand workstations, physical activity, stairwell accessibility - OHS focus on treating issues rather than preventive health approach - Concern colleagues perceive behaviour to be unusual - Concern about disturbing co-workers - Concern that colleagues/managers perceive standing or moving to be unproductive - Supervisor belief that sitting less reduces productivity - Not all levels of management supportive of intervention - Walking during breaks: less time for social interaction Social norms: “So for me there are some hidden pressures, it’s not perceived to be good to be seen walking around unless you’ve got piece of A4 paper in your hand.” Employee, non-intervention study [ 45 ] Disturbing co-workers: “When I’m on the phone standing up I feel a little bit conscious because I feel like I’m shouting out across everyone and I’m sort of distracting people next to me.” Employee, intervention study [ 29 ] Facilitators Facilitators - Workplace culture where sitting less is the norm - Workplace culture supports regular short breaks - Group activities for motivation - Top down (manager, leadership) support and encouragement for sitting less, including permission for change - Having a workplace champion/role model who can motivate others and model behaviour - Organisation interest, investment and commitment in reducing sitting time - Wellbeing committee that meets regularly to discuss raising awareness and strategies - Support from OHS personnel - Having a reason to go and visit colleagues - More supportive social norms for reducing sitting after intervention. - Involvement of co-workers in strategies helped to normalise standing/moving more - Managers providing permission - Management leading by example - Workplace champion driving change Management permission: As soon as managers say, “ If you want to stand, feel free to, ” you can guarantee it there ’ ll be people immediately that will stand because managers have given them that permission to do it and therefore they ’ ve got the permission from everyone else...…”
Section: Resultsmentioning
confidence: 99%
“…If we had, I guess, other tasks that involved getting up for a period of time that would probably help as well.” Employee, non-intervention study [ 12 ] Social or organisational Barriers Barriers - Not wanting to stand out - Concern about disturbing co-workers - Concern that standing or moving perceived as not working by colleagues and managers - Leaders not convinced about benefits of reducing sedentary behaviour - Workplace culture not supportive of initiatives to reduce sitting - Financial investment associated with sit-stand workstations - Culture encourages siloing and use of email. - Cultural issues: “Asian culture” perceives standing to be aggressive - OHS concerns relating to sit-stand workstations, physical activity, stairwell accessibility - OHS focus on treating issues rather than preventive health approach - Concern colleagues perceive behaviour to be unusual - Concern about disturbing co-workers - Concern that colleagues/managers perceive standing or moving to be unproductive - Supervisor belief that sitting less reduces productivity - Not all levels of management supportive of intervention - Walking during breaks: less time for social interaction Social norms: “So for me there are some hidden pressures, it’s not perceived to be good to be seen walking around unless you’ve got piece of A4 paper in your hand.” Employee, non-intervention study [ 45 ] Disturbing co-workers: “When I’m on the phone standing up I feel a little bit conscious because I feel like I’m shouting out across everyone and I’m sort of distracting people next to me.” Employee, intervention study [ 29 ] Facilitators Facilitators - Workplace culture where sitting less is the norm - Workplace culture supports regular short breaks - Group activities for motivation - Top down (manager, leadership) support and encouragement for sitting less, including permission for change - Having a workplace champion/role model who can motivate others and model behaviour - Organisation interest, investment and commitment in reducing sitting time - Wellbeing committee that meets regularly to discuss raising awareness and strategies - Support from OHS personnel - Having a reason to go and visit colleagues - More supportive social norms for reducing sitting after intervention. - Involvement of co-workers in strategies helped to normalise standing/moving more - Managers providing permission - Management leading by example - Workplace champion driving change Management permission: As soon as managers say, “ If you want to stand, feel free to, ” you can guarantee it there ’ ll be people immediately that will stand because managers have given them that permission to do it and therefore they ’ ve got the permission from everyone else...…”
Section: Resultsmentioning
confidence: 99%
“…In another qualitative study, with a convenience sample of 21 employees, self-reported occupational sitting time was 6.4 h ( 20 ). The purpose of the five focus groups was to explore perceptions of health risks associated with prolonged sitting and potential strategies to reduce sitting at work.…”
Section: Resultsmentioning
confidence: 99%
“…One of the barriers to reducing sitting time was the chargeable time culture; everything needs to contribute to the organization's productivity. One respondent cited “Sit at your desk for a lunch break and eat while working.” To change culture, it was recommended to have corporate endorsement of well-being champions and communication at all levels within the organization ( 20 ).…”
Section: Resultsmentioning
confidence: 99%
“…We argue that a focus on employee responsibility will contribute to the belief that obesity is controllable. As controllability beliefs are associated with higher weight stigma (e.g., Teachman et al, 2003 ; Flint et al, 2017 ), such a focus can be expected to result in stigmatization and discrimination toward people with overweight or obesity (e.g., Crandall and Martinez, 1996 ; Crandall et al, 2001 ; Mantler et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%